Fast and efficient acquisition of kinetic data in microreactors using in-line Raman analysis - Schwolow, Sebastian; Rädle, Matthias (Organic process research & development, 2015)
This study demonstrates that a microreactor setup with fast in-line reaction monitoring by Raman spectroscopy can be a highly efficient laboratory tool for kinetic studies and process development. Using a coaxial probe and commercial spectrometer to perform real-time measurements in the microchannel prevents the need for reaction quenching, sampling, and time-consuming off-line analysis methods such as GC or HPLC. A specially designed, temperature-controlled aluminum plate microreactor was developed and tested in the exothermic synthesis of 3-piperidino propionic acid ethyl ester by Michael addition. In-line measurements through a fused quartz screen in the reactor channel, which had an increasing cross-sectional area, allowed time-series kinetic data to be collected over nearly the full range of reaction conversions. An optimum flow rate range in which nearly ideal plug flow behavior can be assumed was identified. Furthermore, a time gradient was applied to the reactant flow rates, and the product concentration was simultaneously and repeatedly measured at various locations in the reactor channel. With this approach, the experiment duration and material consumption are significantly reduced relative to those of conventional steady-state experiments. Two hundred data points with residence times ranging from 0.3 to 49 s were collected in less than 1 h. Thus, this method can be used for the high-throughput screening of reaction parameters in a microreactor.
Gesehen am 13.03.2018